A EXPLORING THE MEDIATING ROLE OF INTRINSIC MOTIVATION IN DIGITAL CULTURE AND LEADERSHIP ON INNOVATIVE PERFORMANCE IN CREATIVE SECTOR: EXPLORING THE MEDIATING ROLE OF INTRINSIC MOTIVATION IN DIGITAL CULTURE AND LEADERSHIP ON INNOVATIVE PERFORMANCE IN CREATIVE SECTOR - Andreas Wijaya; Sophia Susilo (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
The creative industry in Indonesia has undergone significant changes in 2024 due to rapid digital transformation, driven by advancements in technology and shifts in consumer behavior. However, the full potential of digital tools is not yet being realized, as current resources have not been fully optimized to absorb these changes. This highlights the need for a study on the role of intrinsic motivation in employees' ability to foster innovative performance, facilitated by digital leadership and digital culture. The research was conducted among employees working in the digital industry, specifically within the digital-based creative sector. Using Structural Equation Modeling, data were collected from a total of 189 respondents. The study emphasizes the critical roles that digital culture and digital leadership play in enhancing innovative performance within organizations. It demonstrates that both factors significantly contribute to boosting intrinsic motivation among employees, thereby encouraging innovative behaviors